The role of personality and social competence of ppkn teachers in building the nationalist character of junior high school students - Mawara, Ricky; Paotonan, Nesliani (Universitas Tanjungpura, 2025)
Teachers' personal-social competence is often undervalued compared to pedagogical and professional skills, yet it critically impacts student engagement and character development. This qualitative study examines how Civic Education (PPKn) teachers' personal-social competence influences nationalist character formation among junior high school students in Papua's multicultural context. Six PPKn teachers from Abepura District participated as key informants through in-depth interviews. Four key findings emerged: teachers face challenges integrating Papuan cultural narratives with national identity; multiple factors influence nationalism development; personal-social competence varies significantly among teachers; and teacher-student relationships are crucial for character building. Results demonstrate that teachers with strong cultural knowledge, engaging pedagogical approaches, positive interpersonal skills, and authentic role modeling significantly enhance students' nationalist character development. This study contributes to understanding how teacher competencies can bridge local cultural identity with national citizenship in diverse educational contexts